(untitled) (Medical Forum Monthly, 2024)
Background: Acute abdominal pain is one of the most frequently encountered symptoms in patients seeking emergency treatment. Acute and severe abdominal pain, however, is almost always a symptom of intra-abdominal disease. Abdominal pain in neonates, infants, and young children has numerous causes not encountered in adults. Evaluation of mild and severe pain follows the same process, although with severe abdominal pain, therapy sometimes proceeds simultaneously and involves early consultation with a surgeon. History and physical examination usually exclude all but a few possible causes, with final diagnosis confirmed by judicious use of laboratory and imaging tests. Objectives: To find out the most common causes of acute abdomen in the region. Study Design: Retrospective study Place and Duration of Study: This study was conducted at DHQ Teaching Hospital Abbottabad from April 2011 to March 2012 Patients and Methods: Total 1056 patients were admitted with pain abdomen during this period. Patients of all ages were included. Patients with blunt and penetrating trauma to the abdomen were excluded. The patients were divided into 05 age groups. Patients were investigated with physical examination, ultrasonography, X-ray abdomen and blood complete picture, serum amylase and serum LFT’s. Preoperative diagnosis and post operative findings were compared and evaluated. Results: The most common age group was 16-30 yrs (42.5%) and 2nd most common group was 1-15 yrs (28.5%). The most common cause found was acute appendicitis (48.2%). The 2nd common cause was non-specific abdominal pain (16.15%). Total of 645(61%) out of 1056 patients reported with acute abdomen were operated while 411(39%) patients were managed conservatively. Conclusion: Acute appendicitis was the most common cause of pain abdomen in patients of ages 5-30 years followed by non-specific abdominal pain. Life-threatening causes should always be ruled out before focusing on less serious diagnosis. Ultrasonography of abdomen and pelvis should be done routinely in every female patient with acute lower abdominal pain to rule out gynaecological causes of acute abdomen.